Detecting and characterizing fractures in sedimentary deposits with stoneley waves - Escandón, Carlos; Montes, Luis (CT&F - Ciencia, Tecnología y Futuro, 2020)
The naturally fractured reservoirs are attractive potential zones for a successful hydrocarbon prospecting, and the variable density logs (VDL) with Chevron patterns generated by Stoneley waves is a suited tool to characterize fractures. In this project, a simplified algorithm to evaluate fracture location using reflection coefficients and analysis of attenuation was implemented. It also uses a permeability indicator (Stoneley Slowness added by Permeability) to discriminate permeability in fractures. The algorithm was tested in a foot hill well of the Colombian west range, detecting a previously known fractured sandstone zone and indicating its permeability. Besides, the algorithm detected other existent fractures zones with low permeability for production. Previous well flow evaluation of the localized fractures characterized them as low or no permeability fractures.